SEX AND AGGRESSION IN NELSON Mc CORMICK's PROM NIGHT MOVIE (2008); A PSYCHOANALYTIC CRITICISM - WULAN , FEBRIASARI RATNA (2011)
Febriasari Ratna Wulan. A320070309. SEX AND AGGRESSION IN NELSON Mc CORMICK's PROM NIGHT MOVIE (2008); A PSYCHOANALYTIC CRITICISM. Research Paper. Muhammadiyah University of Surakarta. 2011. The major problem in this study is to show sex and aggression in Nelson Mc Cormick's Prom Night movie by using psychoanalytic criticism. It is conducted by analyzing the movie based on its structural elements and based on psychoanalytic criticism. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Prom Night movie directed by Nelson Mc Cormick released in 2008. While the secondary data sources are taken from the books of literary, internet, and other relevant information. Both data are collected through library research and analyzed by descriptive analysis. Using a psychoanalytic criticism as the theoretical framework, the research shows the following findings. First, based on the structural analysis it seems that in this movie, Nelson Mc Cornmick delivers a message about unnatural obsession can cause negative ability until make an aggression to another people. Second, based on psychoanalytic analysis, Nelson wants to convey the psychological phenomena that is a type of personality that leads to sex and aggression